Stage-specific treatment of colorectal cancer: A microRNA-nanocomposite approach - Adewale Oluwaseun Fadaka; Taiwo Akinsoji; Ashwil Klein; Abram Madimabe Madiehe; Mervin Meyer; Marshall Keyster; Lucky Mashudu Sikhwivhilu; Nicole Remaliah Samantha Sibuyi (Elsevier, 2023)
Colorectal cancer (CRC) is among the leading causes of cancer mortality. The lifetime risk of developing CRC is about 5% in adult males and females. CRC is usually diagnosed at an advanced stage, and at this point therapy has a limited impact on cure rates and long-term survival. Novel and/or improved CRC therapeutic options are needed. The involvement of microRNAs (miRNAs) in cancer development has been reported, and their regulation in many oncogenic pathways suggests their potent tumor suppressor action. Although miRNAs provide a promising therapeutic approach for cancer, challenges such as biodegradation, specificity, stability and toxicity, impede their progression into clinical trials. Nanotechnology strategies offer diverse advantages for the use of miRNAs for CRC-targeted delivery and therapy. The merits of using nanocarriers for targeted delivery of miRNA-formulations are presented herein to highlight the role they can play in miRNA-based CRC therapy by targeting different stages of the disease.